Haemodynamic effects of incomplete stent apposition in curved coronary arteries. (3rd October 2017) - Chen, Winson X.; Poon, Eric K.W.; Thondapu, Vikas; Hutchins, Nicholas; Barlis, Peter; Ooi, Andrew
Abstract: Incomplete stent apposition (ISA, also known as malapposition) is a complication that affects day-to-day coronary stenting procedures. ISA is more prominent in complex arterial geometries, such as curvature, as a result of the limited conformability of coronary stents. These malapposed struts disturb the otherwise near-wall laminar blood flow and form a micro-recirculation environment. The micro-recirculation environment is often associated with low wall shear stress (WSS) and upsets the delicate balance of vascular biology, providing possible nidus for thrombosis and restenosis. In this study, a three-dimensional (3D) stent model was virtually deployed into an idealised curved coronary artery. Computational fluid dynamics (CFD) simulations were carried out to systematically analyse the haemodynamic effects of increasing maximum ISA distances, ranging from 180 (moderate), 400 (intermediate) to 910 μ m (severe) in an artery with decreasing radius of curvature (ROC). Micro-recirculations around both proximal and distal malapposed struts become more pronounced as compared to fully-apposed struts. The accompanying areas of low temporally-averaged WSS (AL-TAWSS) can increase twofold compared to the fully-apposed condition. Furthermore, substantial regions (∼5.2% and 9.0%) of AL-TAWSS are detached from the distal end of the malapposed struts in both moderate and intermediate cases respectively. Malapposed stents also induce more variation of TAWSS at the inner bend of the artery. At the stent surface, maximum WSS increases threefold from the fully-apposed case to intermediate ISA. High WSS on the strut surface is known to activate platelets which when exposed to the micro-recirculation environment may lead to their deposition and thrombosis.